Assessment of medical and surgical patients’ satisfaction with nursing care in a general hospital - Ouzounidou, A; Mouderidou, D; Roumbi, M; Sougris, P; Lemonidou, Chryssoula; Merkouris, Anastasios (My University, 2001)
Purpose: To measure medical and surgical patients' satisfaction with nursing care, to compare quantitative and qualitative data and finally to explore possible relationships with background factors. Method: Exploratory, descriptive design with face to face, semi-structured interview of 100 patients from 5 medical and 8 surgical wards with at least 3 days of hospitalization in one big public hospital. Results: The majority of the sample were male (53% - 53) and the mean was age 56 years (SD=18 years). According to quantitative data, the percentage of the satisfied patients ranged from 50% for information and orientation to 95% for the technical aspect of treatment. According to qualitative data, the respective percentages were lower and showed greater variation. Medical patients were more satisfied than surgical (scale from 1 to 4, Mean=3.20 vs 2.97, P<0.01). Education level (r=-0.29, P<0.01) and the use of private nurse (Mean=2.86 vs 3.42, P<0.05) were negatively correlated with the satisfaction with assistance related to the activities of daily life. Patients' expectations were very low, and in many questions, patients tried to justify their dissatisfaction with the lack of nursing personnel. Conclusions: There is a need for continuing measurement of patients’ satisfaction in order to make comparisons and evaluate the nursing interventions. Qualitative data facilitates the interpretation of the quantitative data, gives useful information for the improvement of nursing services and increase the validity of the measurement.